2017
DOI: 10.1002/glia.23167
|View full text |Cite
|
Sign up to set email alerts
|

Acutely damaged axons are remyelinated in multiple sclerosis and experimental models of demyelination

Abstract: Remyelination is in the center of new therapies for the treatment of multiple sclerosis to resolve and improve disease symptoms and protect axons from further damage. Although remyelination is considered beneficial in the long term, it is not known, whether this is also the case early in lesion formation. Additionally, the precise timing of acute axonal damage and remyelination has not been assessed so far. To shed light onto the interrelation between axons and the myelin sheath during de‐ and remyelination, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 39 publications
8
45
0
Order By: Relevance
“…Our observations suggest that APP has a greater role in remyelination rather than in myelin maintenance. This notion is supported by the data showing APP expression was undetectable in healthy axons but accumulated in damaged axons and was significantly upregulated during the early remyelination but decreased gradually during myelination as the proportion of myelinated axons increased (Schultz et al, ). Other evidence supporting APP having a critical role in axon remyelination is obtained in reports showing high levels of APP immunoreactivity in premyelinating oligodendrocyte expressing cells and in demyelinating lesions (Ferguson et al, ; Gehrmann, Banati, Cuzner, Kreutzberg, & Newcombe, ).…”
Section: Discussionmentioning
confidence: 78%
“…Our observations suggest that APP has a greater role in remyelination rather than in myelin maintenance. This notion is supported by the data showing APP expression was undetectable in healthy axons but accumulated in damaged axons and was significantly upregulated during the early remyelination but decreased gradually during myelination as the proportion of myelinated axons increased (Schultz et al, ). Other evidence supporting APP having a critical role in axon remyelination is obtained in reports showing high levels of APP immunoreactivity in premyelinating oligodendrocyte expressing cells and in demyelinating lesions (Ferguson et al, ; Gehrmann, Banati, Cuzner, Kreutzberg, & Newcombe, ).…”
Section: Discussionmentioning
confidence: 78%
“…Post‐mortem MS studies have shown myelin and axonal injury within lesions: However, axons appear to be preserved in remyelinated areas (Schultz et al, ): Crucially, if axons are not remyelinated, axonal degeneration occurs (Lee, Biemond, & Petratos, ; Simons, Misgeld, & Kerschensteiner, ; Singh et al, ). Post‐mortem data from MOG lesions demonstrated demyelination with partial axonal preservation (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other, CSF Aβ reduction could depend on APP deposition around injured axons, although there is no evidence of Aβ deposition in MS plaques. Recent studies showed that APP-expressing axons are partially myelinated, suggesting that acute axonal damage may, at least partially, occur independently from demyelination 24 . In other words, dysregulation of BACE1 and NRG1 might represent the myelin repair processes, while APP expression might be regarded as a biomarker of acute axonal injury.…”
Section: Discussionmentioning
confidence: 99%